ANALISIS PENGETAHUAN DAN KEPATUHAN WAJIB PAJAK UMKM DALAM RANGKA PEMENUHAN KEWAJIBAN PEPAJAKAN PADA PELAKU USAHA UMKM DI KOPERASI BUEKA MADANI CINANGKA TAHUN 2019 - Efendi, Alvian Savinanta; Dewanti, Yopy Ratna (POLITEKNIK LP3I JAKARTA, 2023)
This purpose of this research is to determine lhe level of knowledge and compliance of micro small and medium enterprises (MSME) Taxpayers in Order to fulfill tax obligations on MSME entrepreneurs at the Bueka Madani Cooperatives, Cinangka and the understanding level of MSME Taxpayers about taxation. This research also determines the MSME Taxpayers perceptions on taxation and knowing the constraints faced by MSME Taxpayers in the context of fulfilling the tax obligations of business entities at Bueka Madani Cooperative. This study provided an explanation regarding the phenomenon of fulfilling the tax obligations of MSME business entity using primary data in the form of interviews with the cooperative and MSME Taxpayers which were processed using qualitative descriptive method. The results showed that the level of knowledge and compliance of MSME Taxpayers in fulfilling their tax obligations is still low, therefore, the understanding a n d perception level of MSME Taxpayers about taxation is still very low. The lack of knowledge of MSME taxpayers regarding registering their Tax Identification Number (NPWP), calculation and reporting of income tax for MSME business entities are obstacles to compliance for MSME taxpayers in Cinangka in fulfilling their tax obligations. Keywords: Knowledge, Compliance, Taxation of Entrepreneurs MSME in Cooperatives